2018
DOI: 10.1108/jpcc-02-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

The community school coordinator: leader and professional capital builder

Abstract: Purpose Emerging research demonstrates that the community school model holds promise for meeting the needs of families by improving academic and social-emotional outcomes for students and strengthening communities. In this model, school leaders play an integral role in building relationships among multiple stakeholders, cultivating community partnerships and developing democratic decision making. The purpose of this paper is to focus on the community school coordinator (CSC) as a school leader who carries out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
(18 reference statements)
1
13
0
Order By: Relevance
“…In addition to social brokering, the present study found that schools in the MSIC initiative can be sites for cultural brokering as well. Contributing to research that highlights the important leadership role of family and community liaisons in family engagement and cultural brokering (FitzGerald & Quiñones, 2018;Ishimaru et al, 2016;Yohani, 2011), the present study similarly found the MSIC Community Support Worker and the on-site TDSB Settlement Worker to be key leaders in cultural brokering.…”
Section: (6) Establishing the School As A Social And Cultural Brokersupporting
confidence: 65%
See 4 more Smart Citations
“…In addition to social brokering, the present study found that schools in the MSIC initiative can be sites for cultural brokering as well. Contributing to research that highlights the important leadership role of family and community liaisons in family engagement and cultural brokering (FitzGerald & Quiñones, 2018;Ishimaru et al, 2016;Yohani, 2011), the present study similarly found the MSIC Community Support Worker and the on-site TDSB Settlement Worker to be key leaders in cultural brokering.…”
Section: (6) Establishing the School As A Social And Cultural Brokersupporting
confidence: 65%
“…Parents feeling a sense of trust in their relationships with the school may be an important mechanism of change, as it has been found in a number of studies to be key in schoolfamily-community partnerships and an important factor in determining how welcomed and comfortable parents feel being involved in the school (Barr & Saltmarch, 2014;Bryk & Schneider, 2002;. Building trust is not only the responsibility of principals, but can include other school staff, such as community school coordinators (schoolsupport staff who lead and facilitate partnerships between the school and community), who can also play integral leadership roles in building trust with families (FitzGerald & Quiñones, 2018;Ishimaru et al, 2016). FitzGerald and Quiñones (2018) found that community school coordinators facilitated conversations between school staff and families and acted as someone families could turn to for support, which made families feel they could trust the school and in turn made families feel more comfortable in the school.…”
Section: Partnershipsmentioning
confidence: 99%
See 3 more Smart Citations